PRIMARY HEALTH CARE IN BRAZIL: HISTORICAL TRAJECTORY OF THE FAMILY HEALTH STRATEGY AND ITS ROLE IN ORGANIZING CARE WITHIN THE BRAZILIAN UNIFIED HEALTH SYSTEM (SUS) (REMUNOM, 2026)
This study analyzes the historical trajectory of Primary Health Care (PHC) in Brazil, with an emphasis on the evolution of the Family Health Strategy (FHS) and its role in organizing care within the Unified Health System (SUS). The analysis begins with the historical, political, and institutional milestones that structured PHC, highlighting its consolidation following the Health Reform and the 1988 Federal Constitution, which established the SUS based on the principles of universality, comprehensiveness, and equity. It observes that the creation of the Family Health Program, later consolidated as the FHS, represented a central strategy for reorienting the care model, promoting territorialization, community engagement, and multiprofessional action. It becomes evident that PHC has assumed a strategic role in coordinating care and organizing health care networks, expanding access and strengthening the continuity of health actions. However, challenges related to the fragmentation of services, regional inequalities, structural limitations, and difficulties in integrating the different levels of care persist, impacting the system's effectiveness. It is also important to note that the analysis has limitations due to the lack of empirical data. It is concluded that the consolidation of Primary Health Care (PHC) and the Family Health Strategy (FHS) depends on strengthening systemic integration, improving structural conditions, and reducing inequalities across Brazil.